PENGEMBANGAN MEDIA MOONSTAR (MONOPOLI SUPER PINTAR) PADA TEMA 2 KELAS IV MI AL-FIRDAUS BANDUNG - Siti Ghaida Sri Afira Ruhyadi (Universitas Islam Negeri Raden Fatah Palembang, 2021)
This research was tried in grade IV MI Al-Firdaus Bandung aims to improve education using media facilities Domino smart in thematic subjects